Tinjauan Hukum atas Fungsi OJK dalam Menjamin Perlindungan Tenaga Kerja di Sektor Perbankan Syariah (Lembaga Pengembangan Kinerja Dosen, 2026)
This study examines the role of the Financial Services Authority (Otoritas Jasa Keuangan/OJK) in ensuring the protection of workers in the Islamic banking sector as part of the national financial services system. OJK is not only responsible for maintaining the stability and integrity of the financial industry but also has a role in ensuring the implementation of labor protection principles within financial institutions. This study aims to analyze, from a legal perspective, the functions and authorities of OJK in providing legal protection for workers in Islamic banking and to assess the effectiveness of its supervisory mechanisms. The research employs a normative legal research method using statutory and conceptual approaches, focusing on the analysis of the OJK Law, labor regulations, and legal provisions related to Islamic banking. The findings indicate that OJK has indirect authority in protecting workers through the regulation of corporate governance and risk management practices. However, in practice, the protection of workers in Islamic banking still faces challenges, particularly limited inter-institutional coordination and the absence of optimal preventive supervisory instruments. Therefore, strengthening regulations and enhancing institutional synergy are necessary to ensure fair and sustainable protection for workers in the Islamic banking sector.